THE PORTRAYAL OF BEAUTY MYTH IN MIEKO KAWAKAMI’S NOVEL BREASTS AND EGGS - Lenge, Krensia; Doi, Maksimilianus; Wangga, Febe F I (Lantern: Journal of Language and Literature, 2023)
This study aimed to know the stereotype of beauty myth, the consequence of Professional Beauty Qualification and the vital lies of beauty from the character of Makiko depicted in the novel Breasts and Eggs by Mieko Kawakami through the beauty myth theory. The research design used qualitative research method. This study used beauty myth theory to analyze the myth of beauty that occured in the main character Makiko. The data in this study were taken from quotations such as word, phrases, dialogue and sentences. The results of this study indicate that (1) Makiko the main character experienced the beauty myth cause by the stereotype of beauty that emerged the three assesments of beauty, which is: phisique, mentall, and skill (2) the beauty myth endure by Makiko create the Professional Beauty Qualification (PBQ) standard that cause the consequences of the Professional Beauty Qualification standard in the work, of the six consequences in theory, there are five consequence in this analysis, which is: The PBQ reinforces the double standard, the PBQ reinforces the double standard, the PBQ keep women materially and psychologically poor, it tires women out, it keeps women isolated, and it uses her body to convey her economic role (3) from the consequences of PBQ create the vital lies of beauty.